Back to the future: what digital editors can learn from print editorial practice. - O'Donnell, Daniel Paul (Literary & Linguistic Computing, 2009)
This article revisits the question of the intellectual adequacy of the print critical edition. Contemporary theory and current digital practice have encouraged editors and users of editions to dismiss various aspects of the print critical editionparticularly the reading text and the critical apparatus-as artifacts of an obsolete technology. Using database theory, the author shows how many of these basic elements in fact represent the most intellectually efficient possible way of organizing information about texts and the readings of their underlying witnesses. By recognizing the inherent sophistication of the classical model, digital editors can improve of print practice by exploiting features of the new medium that make it easier to present such data in interactive ways.